IDNLearn.com offers a user-friendly platform for finding and sharing answers. Join our community to access reliable and comprehensive responses to your questions from experienced professionals.
Sagot :
Certainly! Let's solve the equation step-by-step:
Given equation:
[tex]\[ -8 - 3x = 19 \][/tex]
1. Isolate the term with the variable: We need to get the term involving [tex]\( x \)[/tex] by itself. We can start by eliminating the constant term on the left side.
- Add 8 to both sides of the equation to balance it.
[tex]\[ -8 - 3x + 8 = 19 + 8 \][/tex]
- Simplifying the left side, we get:
[tex]\[ -3x = 27 \][/tex]
2. Solve for [tex]\( x \)[/tex]: To isolate [tex]\( x \)[/tex], divide both sides of the equation by -3.
[tex]\[ x = \frac{27}{-3} \][/tex]
- Simplifying the division, we obtain:
[tex]\[ x = -9 \][/tex]
Thus, the solution to the equation [tex]\( -8 - 3x = 19 \)[/tex] is:
[tex]\[ x = -9 \][/tex]
Check:
To verify our solution, substitute [tex]\( x = -9 \)[/tex] back into the original equation:
[tex]\[ -8 - 3(-9) = 19 \][/tex]
Simplify inside the parentheses and multiply:
[tex]\[ -8 + 27 = 19 \][/tex]
Adding the numbers together:
[tex]\[ 19 = 19 \][/tex]
The left side equals the right side, confirming that our solution is correct.
So, [tex]\( x = -9 \)[/tex] is indeed the solution.
Given equation:
[tex]\[ -8 - 3x = 19 \][/tex]
1. Isolate the term with the variable: We need to get the term involving [tex]\( x \)[/tex] by itself. We can start by eliminating the constant term on the left side.
- Add 8 to both sides of the equation to balance it.
[tex]\[ -8 - 3x + 8 = 19 + 8 \][/tex]
- Simplifying the left side, we get:
[tex]\[ -3x = 27 \][/tex]
2. Solve for [tex]\( x \)[/tex]: To isolate [tex]\( x \)[/tex], divide both sides of the equation by -3.
[tex]\[ x = \frac{27}{-3} \][/tex]
- Simplifying the division, we obtain:
[tex]\[ x = -9 \][/tex]
Thus, the solution to the equation [tex]\( -8 - 3x = 19 \)[/tex] is:
[tex]\[ x = -9 \][/tex]
Check:
To verify our solution, substitute [tex]\( x = -9 \)[/tex] back into the original equation:
[tex]\[ -8 - 3(-9) = 19 \][/tex]
Simplify inside the parentheses and multiply:
[tex]\[ -8 + 27 = 19 \][/tex]
Adding the numbers together:
[tex]\[ 19 = 19 \][/tex]
The left side equals the right side, confirming that our solution is correct.
So, [tex]\( x = -9 \)[/tex] is indeed the solution.
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Find the answers you need at IDNLearn.com. Thanks for stopping by, and come back soon for more valuable insights.